2011
DOI: 10.3744/snak.2011.48.6.544
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Added Resistance by Internal Flow Control in the Moonpool of a Drillship

Abstract: The internal flows of moonpool usually causes huge added resistance on drillships, and those are very complex to analyze. Therefore, not only experimental approaches but also numerical simulations are required for better investigations when dealing with the hydrodynamic problems of moonpool. In the present research, numerical simulations are used to find out why the resistance increases by moonpool on a running drillship. That is, the three-dimensional numerical simulations and model tests are carried out to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…) 및 문풀 내부 유동 제 어를 통한 저항 변화 (Choi, et al, 2011), 문풀을 갖춘 드릴쉽의 자항 성능 (Yoo & Choi, 2004 는 압력을 분석하였다 (Wilson, et al, 2001). Table 2는 …”
unclassified
“…) 및 문풀 내부 유동 제 어를 통한 저항 변화 (Choi, et al, 2011), 문풀을 갖춘 드릴쉽의 자항 성능 (Yoo & Choi, 2004 는 압력을 분석하였다 (Wilson, et al, 2001). Table 2는 …”
unclassified
“…Since the mobility of a drillship is enabled by its propulsion system, it can move from one offshore field to another [2]. New emerging drillships are equipped with high capacity dynamic positioning systems.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the figure, the rise of the free surface level increases as the wave length increases. A previous study found that as the average free surface level in a moonpool increases, the added resistance acting on the body of a sailing ship increases (Choi et al, 2011). Therefore, when the wave length is double the ship's length, the hydrodynamic force acting on the moonpool increases along with the added resistance, and therefore, the effect of these phenomena on the propulsion performance of a vessel should be considered synthetically.…”
Section: Analysis Of Hydrodynamic Forcementioning
confidence: 99%
“…In order to determine the characteristics of these self-sustained oscillations, researchers conducted studies on the geometrical shape of the moonpool, the resonance period, and the correlation between the resistance performance and the fluid flow in a moonpool (Kim et al, 2006;Choi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%